2023
DOI: 10.1007/s40266-023-01024-6
|View full text |Cite
|
Sign up to set email alerts
|

The EURO-FORTA (Fit fOR The Aged) List Version 2: Consensus Validation of a Clinical Tool for Improved Pharmacotherapy in Older Adults

Abstract: Background The aging of our societies leads to a higher prevalence of multimorbidity and therefore polypharmacy, which often results in inappropriate drug treatment. To address this issue, numerous listing approaches, such as the Fit fOR The Aged (FORTA) list have been developed. FORTA’s positive impact on the quality of medications and relevant clinical outcomes has been shown. Based on new emerging evidence and experiences with the existing FORTA lists, we aimed to update the FORTA lists in seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…To the best of our knowledge, this is the first consensus study focused on identifying indicators for high-risk and overprescribing of antidepressants. Compared to more generic lists of potentially inappropriate medications [ 23 , 39 ], our focus on a specific class of drugs allowed for the development of a comprehensive set of indicators specifically related to antidepressants. For example, STOPP (Screening Tool of Older Person’s Prescriptions/START (Screening Tool to Alert doctors to Right Treatment) version 3 includes 10 indicators related to antidepressants (7.5%) [ 23 ], while FORTA (Fit fOR The Aged) identifies individual antidepressants for 6 indications [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, this is the first consensus study focused on identifying indicators for high-risk and overprescribing of antidepressants. Compared to more generic lists of potentially inappropriate medications [ 23 , 39 ], our focus on a specific class of drugs allowed for the development of a comprehensive set of indicators specifically related to antidepressants. For example, STOPP (Screening Tool of Older Person’s Prescriptions/START (Screening Tool to Alert doctors to Right Treatment) version 3 includes 10 indicators related to antidepressants (7.5%) [ 23 ], while FORTA (Fit fOR The Aged) identifies individual antidepressants for 6 indications [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to more generic lists of potentially inappropriate medications [ 23 , 39 ], our focus on a specific class of drugs allowed for the development of a comprehensive set of indicators specifically related to antidepressants. For example, STOPP (Screening Tool of Older Person’s Prescriptions/START (Screening Tool to Alert doctors to Right Treatment) version 3 includes 10 indicators related to antidepressants (7.5%) [ 23 ], while FORTA (Fit fOR The Aged) identifies individual antidepressants for 6 indications [ 39 ]. In comparison, this study identified 37 high-risk prescribing indicators related to a broad spectrum of adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of this, drug-related problems were analyzed (e.g., drug-drug interactions, appropriateness of medication [ 18 , 19 ]). For the latter, the PRISCUS [ 20 ] and FORTA list [ 21 ] were used to assess patient-related information.…”
Section: Methodsmentioning
confidence: 99%